DSC Constitutive Modelling of Hydrated Cement Treated Crushed Rock Base as a Road Base Material for Western Australia Roads - Khobklang, Pakdee; Vimonsatit, Vanissorn; Jitsangiam, Peerapong; Nikraz, Hamid (International Committee on Road & Airfield Pavement Technology (ICPT), 2011)
Hydrated Cement Treated Crush Rock Base (HCTCRB) is acommonly used road base material for Western Australia Roads. In order to increase the efficiency of using this material in pavement structure design, material modelling for analysis needs to be investigated. This paper is a preliminary study of the use of the Disturbed State Concept (DSC) to predict the stress-strain relationship for HCTCRB. The DSC equation of HCTCRB has been constructed by using a set of the experimental results of confined compressive strength tests conducted consecutively after the resilient modulus tests. An idealised material model, namely the fully plastic model, of the relative intact (RI) part was considered. The results revealed that the stress-strain relationships, which were back predicted using the DSC modelling, were consistent with the experimental results. The DSC equation, which is suited for analysing the HCTCRB layer in structural pavement, will then be introduced.